In vitro and in vivo toxicological evaluation of 6′-Sialyllactose sodium salt produced by a novel method - Gurung, Rit B.; Dolan, Laurie C.; Arceneaux, Benjamin G.; Go, Hiroe; Park, Eun Jung (Toxicology reports, 2025)
6′-Sialyllactose (6′-SL) sodium salt is the sodium salt of a naturally occurring trisaccharide found in dairy products and human milk. 6′-SL sodium salt formulations produced by different methods have been the subject of other safety studies and are approved for use in food in the United States and other countries. Because the manufacturing process can influence the toxicological profile of a substance, studies were undertaken to assess the safety of 6′-SL sodium salt produced by a novel manufacturing process. The results of genetic toxicity tests (bacterial reverse mutation assay, an in vitro mammalian chromosome aberration test, and an in vivo micronucleus test in mice), and acute and 26-week repeated dose oral toxicity studies in rats for this novel 6′-SL sodium salt are reported herein. All studies were conducted according to Good Laboratory Practice (GLP) and the respective guidelines from the Korean Ministry of Food and Drug Safety (MFDS). The substance showed no evidence of genotoxicity in all three assays that were conducted to address this endpoint and was not acutely toxic to rats at doses up to 6000 mg/kg body weight (bw). The no observed adverse effect level (NOAEL) for toxicity in the 26-week study in both male and female rats was 6000 mg/kg bw/day, the highest dose administered. This new 6′-SL sodium salt is safe in rats at a higher level and for a longer period of time than previously studied in either rats or pigs, demonstrating a more robust safety profile. [Display omitted] •6'-SL sodium salt was prepared by a method that has not been previously described.•It is not genotoxic in the Ames, chromosomal aberration, or micronucleus tests.•The acute oral LD50 value in rats is > 6000 mg/kg bw of 6′-SL sodium salt.•The 26-week oral NOAEL for the substance is 6000 mg/kg bw/day in rats of both sexes.